Prioritizing Tuberculosis Clusters by Genotype for Public Health Action, Washington, USA - Scott Lindquist (Emerging Infectious Diseases, 2013)
Groups of tuberculosis cases with indistinguishable Mycobacterium tuberculosis genotypes (clusters) might represent recent transmission. We compared geospatial concentration of genotype clusters with independent priority rankings determined by local public health officials; findings were highly correlated. Routine use of geospatial statistics could help health departments identify recent disease transmission.